Supportive care needs of women with advanced breast cancer in Ghana. (June 2022) - Akuoko, Cynthia P.; Chambers, Shirley; Yates, Patsy
Abstract: Purpose: Most women with breast cancer in Ghana are initially diagnosed with advanced disease, however, there is limited research about Ghanaian women's experiences of living with advanced breast cancer. The study aimed to understand the perceived (felt) and expressed needs of women with advanced breast cancer. Methods: Using a cross-sectional design, this study assessed the supportive care and spiritual needs, as well as the supportive care service use, of women diagnosed with advanced breast cancer (n = 176) with the Supportive Care Needs Survey-Long Form, the Spiritual Need Assessment for Patients and the modified Client Service Receipt Inventory. Results: Most participants (96.6%) had financial needs and needs in relation to having access to professional counselling. The most prevalent supportive care needs reported were related to health system issues and information needs (90.3%–96.6%). Compared to older women (51.7%), younger women (48.3%) reported greater psychological (p = 0.002) and sexuality needs (p < 0.001) and less religious needs (p = 0.048). Most participants (92.1%) had at least one spiritual need. Many of the available outpatient services were not accessed by the majority of participants (>63%). Conclusions: The study participants reported high supportive care needs even so, most did not access available relevant services. Study findings indicate that most of the participants were unaware of the health and supportive care services that were available to them or that these services were not easily accessible due to their financial status or geographical location. Targeted interventions are needed to assist the women to address their supportive care, spiritual and service needs. Highlights: Women with advanced breast cancer have unmet needs. Limited understanding of women with advanced breast cancer experiences in Ghana. High needs including informational, financial, and spiritual were reported. Barriers to service utilisation impeded access. Target interventions to address the women's supportive care needs highlighting available services.